INTEGRATED MONITORING OF HAZARDOUS GEOLOGICAL PROCESSES IN PRIBAIKALYE: PILOT NETWORK AND FIRST RESULTS - K. Zh. Seminsky; A. A. Dobrynina; S. A. Bornyakov; V. A. Sankov; A. V. Pospeev; S. V. Rasskazov; N. P. Perevalova; I. K. Seminskiy; A. V. Lukhnev; A. A. Bobrov; E. P. Chebykin; I. K. Edemskiy; et al. (Геодинамика и тектонофизика)
The article deals with the first results of integrated geohazard monitoring conducted by the Institute of the Earth’s Crust SB RAS on the territory of Pribaikalye in 2020. The pilot network consists of three sites: "Buguldeika", "Priolkhonye" and "Listvyanka", each of which is equipped with high-precision digital devices including a broadband seismic station, a GPS receiver, deformometers, a sensor of soil radon emanations, and an observation station for the Earth’s electromagnetic environment. This equipment is designed to acquire quantitative information on rock deformation, recent movements and geophysical field variations for solving theoretical and applied problems of geodynamics and seismology, including development of earthquake prediction methods. In the vicinity of the sites, there have been made the hydroisotopic measurements as well as observations over the character of some of exogenous processes. Based on the comprehensive analysis of the seismological, tectonic, deformation and emanation data, acquired also through monitoring, there has been obtained the preliminary characteristics of the Kudarinsky earthquake (December 9, 2020, MW=5.6) that was followed by intensity 5 aftershocks in large cities of the southeastern East Siberia – Irkutsk, Shelekhov, Angarsk, Usolye-Sibirskoe and others. It has been found that the seismic event manifested itself almost in all the fields monitored. This implies the network efficiency for a purposeful study of the precursors of large earthquakes which can initiate the development of other hazardous geological processes in Pribaikalye. The deformation monitoring data show some general patterns of earthquake source evolution which corresponds to the fundamental principles of physical mesomechanics. This opens the prospects for diagnostics of the final phase of earthquake generation in the context of meta-instable state of deformation process and rock mass disintegration.